IMPROVING STUDENTS’ READING COMPREHENSION ON NARRATIVE TEXT BY USING STORY MAP TECHNIQUE - Rosada, Amrina; Rufinus, Albert; bunau, Eusabinus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2015)
Abstract: This thesis is a study on improving students? reading comprehension in narrative text by using Story Map Technique to the tenth grade students of SMA Negeri 10 Pontianak in academic year 2014/2015. The writer took a classroom action research and the teaching learning process took place in two cycles. The subjects of this research were the students of grade X IPA 3 which consist of 39 students. From the observation checklist and field notes, it was found that all the students participated to the activity and did their task well. The students gave positive response to all the explanation and could use the story map technique effectively. For these results, it was concluded that story map technique improved students? reading comprehension skill in narrative text in their Story Map Technique enabled the students to store information in their personal schema more efficiently and facilitated to recall the story elements more completely and accurately. Key words : Story Map technique, reading, narrative text Abstrak : Penelitian ini adaah sebuah studi dalam meningkatkan kemampuan membaca teks naratif dengan menggunakan teknik story map pada siswa kelas X di SMA Negeri 10 Pontianak pada tahun akademik 2014/2015. Penulis melaksanakan peneitian tindakan kelas dan proses pembelajaran dilaksanakan dalam dua siklus. Subjek peneitian adalah siswa pada kelas X IPA 3 yang terdiri dari 39 siswa. Berdasarkan data yang diambil dari embar observasi dan catatan kaki, ditemukan bahwa semua siswa berpartisipasi dalam kegiatan di kelas dan melaksanakan tugas mereka secara baik. Siswa juga memberikan respon yang positif terhadap penjelasan guru dan dapat menggunakan teknik story map secara efektif. Berdasarkan hasil tersebut, dapat disimpukan bahwa teknik story map dapat meningkatkankemampuan membaca naratif teks siswa karena teknik ini membuat siswa mampu untuk memasukan informasi dalam skema mereka sendiri secara lebih efisien dan memfasilitasi siswa untuk mengulas kembali elemen-elemen dalam cerita secara lebih lengkap dan akurat. Kata kunci : teknik Story Map, membaca, teks naratif